1995
DOI: 10.1042/cs0880135
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine Increases Exhaled Nitric Oxide in Normal Human Subjects

Abstract: 1. Endogenous nitric oxide plays an important physiological role and is synthesized by several isoforms of nitric oxide synthase from the semiessential amino acid L-arginine. Nitric oxide is detectable in the exhaled air of normal individuals and may be used to monitor the formation of nitric oxide in the respiratory tract. 2. We have investigated the effect of orally administered L-arginine (0.05, 0.1, 0.2 g/kg) compared with matched placebo on the concentration of nitric oxide in the exhaled air in 23 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 0 publications
4
96
2
Order By: Relevance
“…L-arginine, the substrate for enzymatic NO synthesis, has been shown to increase exhaled NO in a dose-dependent manner when taken orally [42], or infused intravenously [23]. This increase seems to take place primarily in the upper airways [23].…”
Section: Drugsmentioning
confidence: 99%
“…L-arginine, the substrate for enzymatic NO synthesis, has been shown to increase exhaled NO in a dose-dependent manner when taken orally [42], or infused intravenously [23]. This increase seems to take place primarily in the upper airways [23].…”
Section: Drugsmentioning
confidence: 99%
“…We found that glutathione infusion completely prevented hyperglycemiainduced hemodynamic changes and that L-arginine superimposed with ongoing hyperglycemia completely normalized the hemodynamic parameters as well as the baroreflex activity. The evidence for increased release of NO during systemic administration of L-arginine is based on elevation of some indexes of NO synthesis or degradation such as plasma citrulline and cGMP levels (22), urinary nitrate and nitrite (21), and exhaled NO (23). Moreover, similar doses of D-arginine, which is not used for endogenous NO synthesis (24), or L-lysine, which uses the same cationic amino acid transport system as L-arginine (25), have no effect on hyperglycemiainduced vascular changes, at least in normal subjects (7).…”
Section: Conclusion -mentioning
confidence: 99%
“…l-Arg is a safe therapy (Perrine et al, 1994) that has demonstrated the capacity to decrease platelet aggregation (Adams et al, 1995) and reverse endothelial dysfunction (Lerman et al, 1998) in other disease processes and it may represent a new therapeutic intervention in SCD. NO x levels were shown to increase after oral l-Arg supplementation in healthy subjects (Kharitonov et al, 1995). We undertook a study to determine whether oral l-Arg increases NO x production in patients with SCD.…”
mentioning
confidence: 99%